Pengaruh Perencanaan, Pengorganisasian, Pelaksanaan Dan Pengawasan Terhadap Efektivitas Pelayanan Retribusi Persampahan Di Kotapagar Alam - Ancah Andriansah; Hardiyansyah Hardiyansyah; Nisma Aprini (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The aim of this research is to determine and analyze the influence of planning, organizing, implementing and monitoring partially or simultaneously on the effectiveness of waste retribution services in Pagar Alam City. The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests, normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, coefficient of determination, partial tests and simultaneous tests. The research results show that planning has a significant effect on the effectiveness of waste retribution services in Pagar Alam City, organization has a significant effect on the effectiveness of waste retribution services in Pagar Alam City, implementation has a significant effect on the effectiveness of waste retribution services in Pagar Alam City, supervision has a significant effect on the effectiveness of waste retribution services in Pagar Alam City either partially or simultaneously.